Legal Construction of Zakat Transactions through E-Commerce Platforms in Indonesia - Ridho Setiawan Usman (Damhil Law Journal, 2025)
This study examines the legal construction of zakat transactions conducted via e-commerce platforms in Indonesia, focusing on the regulation of digital zakat management, as well as its implications on sharia compliance and legal certainty. Although zakat management is governed by Law No. 23 of 2011, the use of e-commerce platforms for zakat collection still faces a significant regulatory gap, creating serious uncertainty for all parties involved. From a sharia perspective, this study highlights the challenges in fulfilling the pillars and conditions of zakat such as intention (qasad), ownership transfer (tamlik), and accurate verification of mustahiq (eligible recipients), which are vulnerable to disruption by digital mechanisms. The research employs a normative legal methodology with literature review and case analysis to formulate a legal construction integrating positive law principles and sharia provisions. The findings indicate an urgent need for updated regulations that are adaptable to technology, emphasizing transparent governance mechanisms, accountability, and digital consumer protection. A comprehensive legal framework is expected to provide legal certainty and sharia legitimacy, promoting the optimization of zakat potential through digital technology as an instrument for poverty alleviation and empowerment of the Muslim community in the modern era.